Effects of Plant Population in Cassava (Manihot Esculenta Crantz) as Influenced by Planting Methods - Hussain, Khelikuzzaman Meera (1982)
The effects of two planting methods (20 cm cutting planted horizontally and 60 cm cuttings planted vertically) and plant populations ranging from 5,000 to 40,000 plants per hectare on the performance of two cassava varieties were investigated. The relationships of yield and yield components with plant populations were examined by fitting linear and quadratic regression equations to each planting method and variety. Results of the experiment show that in both varieties, the horizontal planting yielded significantly better than vertical planting in terms of root and starch yields. The increase in root yield wit variety MVen 119 was due to both increase in total root number and harvest index. In variety MCol 673 the increase in root yield was attributed mainly to increase in harvest index and decrease in shoot number. Variety MVen 119 out yielded MCol 673 in terms of root yield but the difference in starch yields between the two varieties was not evident. However, variety MCol 673 is favoured because of its higher starch content. The yield response of the treatments to plant population showed that root yield declined with in creasing plant population and that the yield was highest for the lowest population tested in the study. Yield reduction at high plant populations was generally attributed to the production of excessive shoots as well as to the decrease in mean root weight and mean root length. Root number was enhanced by planting horizontally and it also showed an increasing trend with plant population which had been as-certained to be quadratic.